Analisis Kebutuhan Bahan Ajar Berbasis Google Sites dalam Pembelajaran Sejarah Kelas XI SMA Pembangunan Laboratorium UNP - Aldawiah, Rabia; Yefterson, Ridho Bayu (Jurnal Kronologi, 2025)
This study is motivated by preliminary data indicating that many students struggle to sequence historical events and compare past events with those occurring in the present. This reflects a low level of students' chronological thinking ability. In addition, interview results revealed that history learning has not yet utilized teaching materials capable of strengthening this skill while also addressing 21st-century learning challenges. The purpose of this study is to analyze the needs for developing digital teaching materials based on Google Sites in history learning for eleventh-grade students at SMA Pembangunan Laboratorium UNP. This research employed a descriptive qualitative approach, with data collected through diagnostic tests, interviews with students and teachers, and documentation of current teaching materials. The findings show that students require teaching materials that are visual, interactive, and not merely text-based. Teachers also experience difficulties in developing teaching materials due to limited technological skills. Therefore, Google Sites is considered a relevant platform to meet these needs, as it can integrate various multimedia elements flexibly and support students